A multicenter clinical evaluation of polymerase chain reaction coupled with quantum dot fluorescence analysis in pathogen detection for patients with suspected bloodstream infections - Guangzhi Du; Wenjie Yang; Bangxing Lin; Xinghan Huang; Junjie Lao; Yueming Chen; Xueyan Dong; Lihui Xu; Xianjun Wang (Microbiology Spectrum, 2026)
Bloodstream infections remain a serious clinical challenge and are associated with substantial morbidity and mortality, particularly in critically ill patients. Early identification of the causative pathogens is essential for timely antimicrobial therapy, yet conventional blood culture methods often require prolonged incubation and additional processing time before results become available. In this study, we evaluated the clinical performance of polymerase chain reaction coupled with quantum dot fluorescence analysis (PCR-QDFA) for pathogen detection in patients with suspected bloodstream infections. The assay showed strong agreement with routine culture-based identification while providing results in a much shorter time. Its ability to simultaneously detect multiple common bloodstream pathogens makes it suitable for use in routine diagnostic laboratories. Rapid pathogen identification through PCR-QDFA may help clinicians make earlier treatment decisions, support more appropriate antimicrobial use, and improve the overall management of bloodstream infections.